2016
DOI: 10.5455/medarh.2016.70.373-378
|View full text |Cite
|
Sign up to set email alerts
|

Does Remote Ischaemic Preconditioning Protect Kidney and Cardiomyocytes After Coronary Revascularization? A Double Blind Controlled Clinical Trial

Abstract: Objective:To investigate efficacy of remote ischaemic preconditioning on reducing kidney injury and myocardial damage after coronary artery bypass grafting surgery (CABG).Background:Ischaemic preconditioning of a remote organ reduces ischaemia-reperfusion injury of kidney and myocardium after CABG.Method:To reduce myocardial damage and kidney injury by applying Remote Ischaemic Preconditioning we recruited 100 consecutive patients undergoing elective coronary artery bypass grafting surgery. We applied three cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Remote ischemic conditioning (RIC) by brief episodes of ischemia/reperfusion in parenchymal organs or limbs before (remote ischemic preconditioning; RIPC) or during (remote ischemic perconditioning) sustained myocardial ischemia and subsequent reperfusion is a non-invasive strategy to protect the myocardium from irreversible ischemia/reperfusion injury. The protection by RIC has been demonstrated in many experimental studies and confirmed in patients undergoing elective interventional 1 or surgical coronary revascularization 2 5 and in patients with reperfused acute myocardial infarction 6 10 . The efficacy of RIC was established by a reduction in cardiac biomarker release 1 5 , 9 or by cardiac imaging 6 8 , 10 and resulted in improved short-term 4 , 7 and long-term clinical outcome 1 , 3 , 11 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Remote ischemic conditioning (RIC) by brief episodes of ischemia/reperfusion in parenchymal organs or limbs before (remote ischemic preconditioning; RIPC) or during (remote ischemic perconditioning) sustained myocardial ischemia and subsequent reperfusion is a non-invasive strategy to protect the myocardium from irreversible ischemia/reperfusion injury. The protection by RIC has been demonstrated in many experimental studies and confirmed in patients undergoing elective interventional 1 or surgical coronary revascularization 2 5 and in patients with reperfused acute myocardial infarction 6 10 . The efficacy of RIC was established by a reduction in cardiac biomarker release 1 5 , 9 or by cardiac imaging 6 8 , 10 and resulted in improved short-term 4 , 7 and long-term clinical outcome 1 , 3 , 11 .…”
Section: Introductionmentioning
confidence: 81%
“…The protection by RIC has been demonstrated in many experimental studies and confirmed in patients undergoing elective interventional 1 or surgical coronary revascularization 2 5 and in patients with reperfused acute myocardial infarction 6 10 . The efficacy of RIC was established by a reduction in cardiac biomarker release 1 5 , 9 or by cardiac imaging 6 8 , 10 and resulted in improved short-term 4 , 7 and long-term clinical outcome 1 , 3 , 11 . However, two large-scaled randomized trials in patients undergoing cardiac surgery, ERICCA 12 and RIPHeart 13 , were neutral and did not confirm reduced biomarker release and improved clinical outcome with RIPC.…”
Section: Introductionmentioning
confidence: 81%
“…Remote ischemic conditioning by repetitive limb ischemia/reperfusion also reduces myocardial damage in patients undergoing elective interventional2 or surgical coronary revascularization3, 4, 5, 6 and in those with reperfused acute myocardial infarction 7, 8, 9, 10, 11, 12, 13. Cardioprotection was confirmed by reduced release of cardiac biomarkers2, 3, 4, 5, 6, 10 or by increased salvage in cardiac imaging7, 8, 9, 11 but also resulted in improved short‐5, 8 and more long‐term2, 4, 13, 14, 15 clinical outcome in retrospective analyses. Recently, the first prospective, randomized trial on patients with reperfused acute myocardial infarction confirmed improved clinical outcome as a primary end point of remote ischemic conditioning during follow‐up for 3.6 years 13.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of myocardial ischemia/reperfusion injury by remote ischemic conditioning has been demonstrated in patients undergoing elective interventional 5 or surgical coronary revascularization 6 9 , and in patients with acute myocardial infarction 10 15 . The protection was confirmed by a reduction in cardiac biomarker release 5 9 , 14 or by cardiac imaging 10 , 12 , 13 , 15 , and it was associated with improved short- 8 , 12 and long-term clinical outcome 5 , 7 , 11 . In contrast, two recent large-scaled randomized trials in patients undergoing cardiac surgery, ERICCA and RIPHeart, failed to confirm reduced biomarker release and improved clinical outcome with remote ischemic preconditioning (RIPC) 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%